Association between aortic telomere length and cardiac post-transplant allograft function. (1st September 2019) - Dlouha, Dana; Vymetalova, Jevgenija; Hubacek, Jaroslav A.; Lanska, Vera; Malek, Ivan
Abstract: Background: In patients having undergone orthotopic heart transplantation, a number of complications exist that are known to be connected to both telomerase activity and telomere length. The aim of this study was to determine how telomere length in aortic DNA correlates with the subsequent post-transplantation development of the patients. Materials and methods: Between 2005 and 2015, we collected aortic samples from 376 heart recipients (age 50.8 ± 11.8 years) and 383 donors (age 38.6 ± 12.2 years). Relative telomere length in aortic tissue DNA was determined using quantitative PCR. Results: Shorter telomere length was detected in heart allograft recipients compared to donors ( P  < 0.0001). Patients suffering acute cellular rejection had significantly shorter telomere length ( P  < 0.01) than patients without rejection. Shorter telomere length was observed in patients with implanted mechanical circulatory support before heart transplantation ( P  < 0.03), as well as in subjects with cardiac allograft vasculopathy ( P  < 0.05). Overall survival time after heart transplantation was associated with shorter donor telomeres ( P  < 0.004). Conclusions: Telomere length differed between donors and recipients independent of the sex and age of the patients. Our findings suggest a potential new linkage between the aortic telomere length of recipients and post-heart transplant complications. Further studies focusing on epigenetic modifications and gene regulation involved in telomere maintenance in transplanted patients should verify our results. Highlights: Reduced telomere length is a marker of cellular senescence. Aortic telomere length differs between donors and recipients independently of age. Recipient shorter aortic telomere length is in relationship with the higher occurrence of acute cellular rejection in donors. Recipients with implanted left ventricular assist device exhibit reduced aortic telomere length. Donor shorter telomere length is associated with overall survival time.